Factors associated with symptoms of physical and emotional burden in informal caregivers of the elderly - Leandro Corrêa Figueiredo; Gustavo Carrijo Barbosa; Diana Quirino Monteiro; Gabriela Martins; Adrielli Fernanda de Oliveira e Silva; Luana Flávia Talmelli Ruy; Tatiana de Oliveira Sato; Aline Cristina Martins Gratão (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to analyze the personal and work-related burden factors associated with physical and emotional symptoms of informal caregivers of the elderly. Methods: cross-sectional study conducted with 121 informal caregivers and 121 seniors who received care, assessed individually for the risk of: physical overload, musculoskeletal symptoms, Self-Reporting Questionnaire, effort perception, and Katz index. Results: a greater perception of effort raises up to 3.3 times the chances of presenting symptoms of pain in the spine region (p=0.01), and lower functional capacity of the elderly increases up to 1.3 times the chances of presenting pain symptoms in the spine region (p=0.02). The symptoms of emotional overload were associated with the caregiver's low income (p=0.02). Conclusions: the perception of effort, dependence of the elderly, caregiver's age, and symptoms of emotional overload are involved with caregivers' symptoms of physical overload, and low income, with emotional overload.